Integrated Marketing Communication Strategy of Tourism Awarness Groups in Order to Promote Tourism Village - Sukma, Putri; Herna (LPPM Stikosa - AWS, 2024)
The tourism industry has an important role as one of the driving forces of national economic growth. One of them is Kelawi Tourism Village in Lampung. The tourism village is managed by tourism awareness groups (Pokdarwis) which are individuals who have an interest and care about the development of local tourism based in rural areas. The purpose of this study is to analyze the integrated marketing communication strategy carried out by Pokdarwis Minang Rua Bahari in an effort to promote Kelawi Tourism Village. This research uses the constructivism paradigm with a qualitative descriptive approach and case studies as the method. Data collection techniques are carried out by in-depth interviews, observation and analysis of related documents. The results showed that in an effort to develop tourism potential in Kelawi Tourism Village, an integrated marketing communication strategy was applied consisting of three stages of the process, namely planning, implementation, and evaluation. The planning phase begins with the identification of the target audience. Pokdarwis Minang Rua Bahari implements various forms of integrated marketing communication in the implementation stage by adopting the concept of 8 promotion mixes using the concept of promotion mix including advertising, personal sales, sales promotion, public relations and publications, interactive marketing, events and experiences, word of mouth marketing, and direct sales. In its implementation, Pokdarwis has not formulated an integrated marketing communication strategy in a comprehensive, integrated, and sustainable manner. This is a form of evaluation carried out periodically as a basis for continuous promotional steps.